Effects of Internal and External Attentional Focus on Postural Response to a Sliding Stance Surface. Issue 3 (June 2019) - Kunimura, Hiroshi; Matsuoka, Masakazu; Hamada, Naoki; Hiraoka, Koichi
The present study examined whether an internal or external attentional focus would affect participants' feet-in-place balance response to postural stance perturbations. A movable platform automatically slid forward or backward while healthy participants stood on it and (a) performed no cognitive activity (control), (b) focused on the pelvis or upper body sway (internal focus), (c) memorized a number displayed immediately before the platform slid (external focus), or (d) kept the equilibrium of an unstable cylinder over the arm (external focus). The forward displacement of the pelvis induced by the platform sliding forward was smaller when participants focused on their pelvic sway, although such effect was absent when they focused on their upper body sway, indicating that the internal focus was effective for the postural response when attention was paid to the pelvic sway. Regarding an external attention focus, the forward displacement of the pelvis induced by the platform sliding forward was smaller when participants focused on the equilibrium of an unstable object over the arm, but this effect was absent when they focused on the number, indicating that an external focus was only effective when the unstable object focused upon was relevant to the equilibrium of one's own body. No attentional intervention was effective during backward sliding of the support surface, indicating that central set for responding to postural perturbation depends on the direction of the postural perturbation.